Trial watch: Dendritic cell-based anticancer immunotherapy - Abhishek D. Garg; Monica Vara Perez; Marco Schaaf; Patrizia Agostinis; Laurence Zitvogel; Guido Kroemer; Lorenzo Galluzzi (OncoImmunology, 2017)
Dendritic cell (DC)-based vaccines against cancer have been extensively developed over the past two decades. Typically DC-based cancer immunotherapy entails loading patient-derived DCs with an appropriate source of tumor-associated antigens (TAAs) and efficient DC stimulation through a so-called “maturation cocktail” (typically a combination of pro-inflammatory cytokines and Toll-like receptor agonists), followed by DC reintroduction into patients. DC vaccines have been documented to (re)activate tumor-specific T cells in both preclinical and clinical settings. There is considerable clinical interest in combining DC-based anticancer vaccines with T cell-targeting immunotherapies. This reflects the established capacity of DC-based vaccines to generate a pool of TAA-specific effector T cells and facilitate their infiltration into the tumor bed. In this Trial Watch, we survey the latest trends in the preclinical and clinical development of DC-based anticancer therapeutics. We also highlight how the emergence of immune checkpoint blockers and adoptive T-cell transfer-based approaches has modified the clinical niche for DC-based vaccines within the wide cancer immunotherapy landscape.